Predictors of dual control of HIV and diabetes. Issue 9 (1st September 2016) - Zuniga, Julie; Nguyen, Minh Ly; Holstad, Marcia
ABSTRACT: Diabetes is one of the most frequently diagnosed comorbidities in individuals living with HIV. Dual control of both conditions is essential because both diseases negatively impact the immune and vascular systems. The purpose of this retrospective study was to assess the factors associated with dual control of HIV and diabetes. Patients from a large urban Ryan White-funded HIV clinic with a diagnosis of diabetes were identified; inclusion criteria comprised age over 25 years, use of antiretroviral therapy for at least 6 months, and a diagnosis of diabetes. Optimal control was described as a non-detectable viral load (i.e. log10 HIV1-viral load <1.6) and HbA1c ≤7%. Fewer than half of 186 patients had optimal control of HIV and diabetes. Direct logistic regression using backward stepwise entry identified three variables that significantly fit the model: age, insulin-based therapy, and African-American race. The full model was statistically significant. As patients with HIV now live longer, more effort needs to be given to adherence to improve health outcomes for co-morbidities.